Memory struggles : remembering the apartheid era by University of Natal medical alumni, 1990s to the early 2000s (Historia, 2021)
The University of Natal's Medical School opened in the city of Durban in 1951 and was one of the first in the country to train black students from diverse backgrounds as doctors in apartheid South Africa. This article, however, steps back from trying to capture this school's social history, to reflect on the issue of memory, especially the constructed nature of memories produced by alumni who studied at this institution during the apartheid period. The first part of this article considers the common memory narratives produced in written and oral accounts in the 1990s. In this period, celebratory narratives that stressed students' "unity in adversity" and anti-apartheid "struggle" activities were publicly privileged and commonly remembered. However, as the second part shows, in more recent years, critical memories have surfaced in public to challenge these triumphant narratives. In the early 2000s, memories highlighting issues of controversy and division amongst students have burst into the public domain. Reasons for these memory shifts as well as the changing historical contexts influencing their production are considered in this article. There is also an analysis of how memory production adds another critical approach for the researcher exploring institutional histories. Die Universiteit van Natal se Mediese Skool het in die stad Durban in 1951 geopen en was een van die eerste in die land om swart studente op te lei as dokters in apartheid Suid-Afrika. Hierdie artikel beweeg egter weg van die poging om hierdie skool se sosiale geskiedenis vas te lê, en probeer om te besin oor die kwessie van geheue, veral die gekonstrueerde aard van herinneringe van alumni wat tydens die apartheid tydperk aan hierdie instelling gestudeer het. Die eerste deel van hierdie artikel beskou die gemeenskaplike geheue verhale wat in skriftelike en mondelinge vorm in die 1990's verskyn het. In hierdie tydperk is feestelike verhale wat studente se "eenheid in swaarkry" en hul anti-apartheid "struggle" aktiwiteite in die openbaar beklemtoon het bevoorreg en onthou. Maar, soos die tweede deel wys, het in meer onlangse jare, kritiese herinneringe in die openbaar verskyn wat hierdie triomfantelike vertellings uit gedaag het. In die vroeë 2000's het herinneringe wat kwessies van omstredenheid en verdeeldheid onder studente beklemtoon in die openbare domein uitgebars. Ek ondersoek die redes vir hierdie veranderinge in geheue asook die veranderende historiese kontekste wat hul produksie beïnvloed het. Verder besin ek oor hoe die analise van die produksie van geheue nog 'n kritieke laag byvoeg tot die navorser se ondersoek van institusionele geskiedenis.
Keywords: Production of history; University of Natal; Apartheid; Durban Mediese Skool; Post-apartheid